A Comparative Study of Chronic Subdural Hematoma in Patients With and Without Head Trauma: A Retrospective Cross Sectional Study - Ou, Yunwei; Yu, Xiaofan; Liu, Xiaojuan; Jing, Qian; Liu, Baiyun; Liu, Weiming (Frontiers in Neurology, 2020)
Background: The clinical features of chronic subdural hematomas (CSDHs) in patients with and without a history of head trauma have remained unclear. Here, we investigated differences in clinical characteristics in CSDH patients with and without head trauma. Methods: We retrospectively collected clinical characteristics of CSDH patients who had undergone exhaustive drainage strategies via burr-hole craniostomies from August 2011 to May 2019. We divided patients into a trauma group (i.e., head trauma) and a no-trauma group. Chi-square tests or t-tests were used to analyze differences in clinical characteristics between the two groups. Multiple linear regression analysis was performed to analyze the relationships between the clinical characteristics and either reduction of the hematoma cavity or length of the hospital stay in CSDH patients with trauma. Results: We collected data from 1,307 CSDH patients, among whom 805 patients had a history of head trauma whereas 502 patients did not. The mean age of patients with head trauma was 64.0 ± 16.1 years, while that of patients without head trauma was significantly younger at 61.5 ± 17.9 years (p = 0.010). Furthermore, more patients in the no-trauma group had a history of hypertension compared to those in the trauma group (40.2 vs. 32.9%, p = 0.007). Dizziness occurred in 29.2% of patients with trauma and in 23.1% of patients without trauma (p = 0.016). A greater number of patients with trauma showed a reduction of hematoma cavity after surgery compared to that of patients without trauma (p = 0.002). The length of hospital stay in patients with trauma was 7.9 ± 4.5 days, which was longer than that of patients without trauma (7.3 ± 3.7 days, p = 0.016). In contrast, there were no significant different differences between the two groups in terms of the densities of hematomas on computed-tomography scans, complications, mortality rates, recurrence rates, or outcomes. Conclusion: Our findings indicate that there were some noteworthy differences in the clinical and pathogenic characteristics of CSDH patients with and without head trauma. However, our findings also indicate that if an optimal treatment method is employed, such as our exhaustive drainage strategy, similar treatment outcomes can be achieved between these groups.